2014
DOI: 10.1071/mf13167
|View full text |Cite
|
Sign up to set email alerts
|

Photosynthetic responses to submergence in mangrove seedlings

Abstract: Flooding and salinity fluctuations are common in mangrove systems. Sometimes these events are long-lasting, persisting several months. With an increased frequency of heavy rainfalls and terrestrial run-off, subsequent floods have been associated with massive mangrove mortality and failure to regenerate in the region. Owing to climate change, these events are expected to be more common in the future. We investigated how three weeks of submergence in water of different salinities affected the photosynthetic rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 22 publications
1
15
1
Order By: Relevance
“…Abou Jaoude et al (2013) have found that saltwater flooding damages plants more severely than freshwater flooding, and Naumann et al (2008) reported that net photosynthesis decreased significantly more after three-days submergence in saltwater compare to freshwater submergence. Interestingly, our results showed a negative effect of seawater in plants that were shallowly submerged for a relatively short period of time, and thus expand previous effects found after a long period of submergence in profundity (Mangora et al, 2014). However, because our design does not include a freshwater submergence treatment, we cannot identify the source (submergence or salinity) of the negative effect encountered in plants under seawater submergence conditions.…”
Section: Discussioncontrasting
confidence: 43%
“…Abou Jaoude et al (2013) have found that saltwater flooding damages plants more severely than freshwater flooding, and Naumann et al (2008) reported that net photosynthesis decreased significantly more after three-days submergence in saltwater compare to freshwater submergence. Interestingly, our results showed a negative effect of seawater in plants that were shallowly submerged for a relatively short period of time, and thus expand previous effects found after a long period of submergence in profundity (Mangora et al, 2014). However, because our design does not include a freshwater submergence treatment, we cannot identify the source (submergence or salinity) of the negative effect encountered in plants under seawater submergence conditions.…”
Section: Discussioncontrasting
confidence: 43%
“…A number of studies show species-specific tolerances to prolonged water logging [37][38][39][40]. Common mangroves, such as Avicennia marina, exhibit a high degree of tolerance to water logging, but responses are highly variable in relation to length and water depth of immersion, salinity, temperature, and other environmental factors [41,42].…”
Section: Modern Evidencementioning
confidence: 99%
“…Mangroves vary greatly in how they respond to a sea level rise and the effect of tidal flooding and such responses appear to be species-specific [52]. For example, Avicennia marina is highly tolerant to prolonged water logging, but responses are highly variable in relation to the water depth of immersion and the length of time as well as salinity, temperature, and other environmental factors [54,55]. There may be other biological responses of mangroves to waterlogging.…”
Section: Rising Sea-levelmentioning
confidence: 99%